The Influence of Perceived CSR Authenticity on Perceived Brand Loyalty Through Perceived Brand Authenticity in the Fast Fashion Industry - Andani Fanza Florent Dachi (International Journal Labs, 2023)
The fast fashion model business has represented a profound revolution for the fashion industry over the past few decades. The term